Reconstruction of the Rules on Compensation in the Termination of a Fixed-Term Employment Agreement in a Fair Manpower Manpower Agreement: Analysis of Article 62 of Law Number 13 of 2003 concerning Manpower - Yose Desman; Megawati Barthos (Al-Makki Publisher, 2025)
The study discusses the urgency of reconstructing the provisions on compensation in Fixed-Term Employment Agreement (PKWT) termination as regulated in Article 62 of Law Number 13 of 2003 concerning Manpower. These provisions are deemed unjust and lack legal certainty because they do not explain in detail the elements of compensation, do not determine the implementation mechanism, and have minimal sanctions for violations. In practice, PKWT workers are often the most disadvantaged parties when there is a unilateral termination of employment by employers. By using normative legal research methods and conceptual and legislative approaches, this study analyzes the weaknesses of Article 62 norms and proposes a new formulation that is fairer, more balanced, and implementable. The recommendations submitted include an explanation of compensation forms, payment procedures, administrative sanctions, and strengthening the mechanism for supervision and dispute resolution. The results of this study are expected to contribute to the renewal of labor law that supports the protection of the rights of contract workers.